Design, fabrication, and radio frequency property evaluation of a through-glass-via interposer for 2.5D radio frequency integration. (22nd May 2019) - Cai, Han; Yan, Jun; Ma, Shenglin; Luo, Rongfeng; Xia, Yanming; Li, Jiwei; Hu, Liulin; He, Shuwei; Tang, Zhongjun; Jin, Yufeng; Wang, Wei; Chen, Jing
Abstract: In this paper, a through-glass-via (TGV) interposer for 2.5D radio frequency (RF) integration is presented. A coplanar waveguide (CPW) transmission line with grounded TGVs on one side interconnects with the mounted RF devices, and an electrical ground plane on the other side. Tapered TGVs are fabricated using a combined method of sandblasting and thinning/polishing process to achieve precise control of the profile of the vias and improve uniformity. The TGVs are metalized by conformal copper (Cu) electroplating to form a vertical interconnection between the upper and lower metal layers, which can maintain RF performance and avoid thermal stress issues. The CPW transmission lines with electrically grounded TGVs and test structures are designed, fabricated and tested to evaluate the TGV's RF performance and suitability for 2.5D RF integration. The RF measurements show that the insertion loss is about 0.13 dB mm −1 @10 GHz for the CPW line with grounded TGV which is less than 0.1 dB@10 GHz for a single TGV. We analyzed S parameter for the tests and simulations when taking into account various factors in the manufacturing process, such as the surface roughness and metal resistivity. The results provide a research direction for the optimization of the parameters in the follow-up study. In addition, a 2.5D RF receiver module based on the proposed TGV interposer in the L-band is assembled and validated. The gain value of the TGV interposer integrated RF module is about 14.4 dB, which is close to the theoretical value.